Stakeholder collaboration to build peace through public interest relations (PIR) (Study on the commemoration of Suran Agung conflict in Madiun) - Johan, Rediaz Rakhman; Hastjarjo, Sri; Satyawan, Ignatius Agung (Universitas Negeri Yogyakarta, 2020)
Madiun Regency is one area that has a lot of active silat colleges, there are 14 (fourteen) silat colleges, mostly based in Madiun. In the dynamics of Madiun pencak silat development, there is Suran Agung tradition as a form of local wisdom in every pencak silat college at the suro month. The activity involved mass mobilization, the escalation of conflict between members of the martial arts college and communities also increased. The history of the conflict began when there was fanaticism of teachings from the Ki Ngabei Soerodiwiryo students. Conflicts that occurred in the Suran Agung involved between groups of fighters and community which often caused material losses such as throwing stones, destruction of public facilities also lead to violence resulting in casualties. Qualitative research here to analyze the efforts of the District Government of Madiun in preventing conflict that is an issue for the public, the Public Interest Relations (PIR) approach to the practice of Suran Agung in Madiun focuses on stakeholder collaboration in peace efforts. The result of PIR practice is the emergence of a new identity for Kampung Pesilat Indonesia as a milestone for peace in social change to realize the vision and mission of regional head.